Another look at LaTeX to SGML conversion - Rahtz, S (TeX Users Group, 1995)
Publishers are starting to use SGML as their permanent form of storage for documents. How can LaTeX files be converted to an SGML instance? This paper discusses possible strategies, and describes and implementation by Elsevier Science of a system based on coversion in TeX itself, and extraction of SML code from the dvi file.